Utilization of nanoparticle soybean extract as an extracellular cryoprotectant in cooling semen of Bali cattle (Bos indicus) - Dian Ratnawati; Gatot Ciptadi; Sri Rahayu; Dita Retnowulan; Fardha Ad Durrun Nafis; Taufiq Ridwan; Achmad Setiyono; Iswati Iswati; Yuli Arif Tribudi; Sulistiyoningtiyas Irmawanti; Trinil Susilawati (Journal of Applied Animal Research)
This research aimed to evaluate the effectiveness of Caudal Epididymis Plasma (CEP) combined with nanoparticle soybean extract (NSE) as diluents in maintaining the quality, motility and DNA integrity of Bali cattle spermatozoa in liquid semen. The study utilized semen from Bali cattle and employed a Randomized Complete Block Design (RCBD). Four treatment groups were tested: T1 (CEP + 10% Egg Yolk), T2 (CEP + 40% NSE), T3 (CEP + 50% NSE) and T4 (CEP + 60% NSE). The observed parameters included sperm motility, viability, abnormalities, membrane integrity, Superoxide Dismutase (SOD), Malondialdehyde (MDA), DNA fragmentation and Scanning Electron Microscope (SEM) morphology. Motility, viability, abnormalities and membrane integrity were analyzed using ANOVA via SPSS 16, while SOD, MDA and DNA fragmentation were assessed using Microsoft Excel; SEM results were interpreted descriptively. The findings revealed that T4 had significantly higher abnormalities (18.81%) compared to other groups (p < 0.05). However, T3 and T4 showed superior progressive motility on day 9 of cold storage. Higher SOD and MDA levels were found in T1 on day 7. DNA fragmentation remained low across all treatments, ranging from 3.65% to 5.35%. The use of CEP with 50-60% NSE effectively preserved semen quality for up to nine days of storage.